2014
DOI: 10.1002/ijc.29089
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal liver metastases with a disrupted circadian rhythm phase shift the peripheral clock in liver and kidney

Abstract: Circadian clock genes regulate 10-15% of the transcriptome, and might function as tumor suppressor genes. Relatively little is known about the circadian clock in tumors and its effect on surrounding healthy tissues. Therefore, we compared the 24-hr expression levels of key circadian clock genes in liver and kidney of healthy control mice with those of mice bearing C26 colorectal tumor metastases in the liver. Metastases were induced by injection of C26 colorectal carcinoma cells into the spleen. Subsequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 44 publications
2
50
0
6
Order By: Relevance
“…Arrhythmic liver metastases of colorectal cancer phase-shift the expression of clock genes in healthy liver tissue. Similar phase shifts, most likely caused by some humoral factors, were also observed in more distal organs such as kidney [126]. Moreover, a recent study reports that mice bearing adenocarcinomas in lung show an altered hepatic circadian metabolism.…”
Section: Cancer Affects Circadian Rhythms In Cells and In The Bodymentioning
confidence: 59%
“…Arrhythmic liver metastases of colorectal cancer phase-shift the expression of clock genes in healthy liver tissue. Similar phase shifts, most likely caused by some humoral factors, were also observed in more distal organs such as kidney [126]. Moreover, a recent study reports that mice bearing adenocarcinomas in lung show an altered hepatic circadian metabolism.…”
Section: Cancer Affects Circadian Rhythms In Cells and In The Bodymentioning
confidence: 59%
“…Previously, WEE1 expression was increased in metastatic melanomas compared with primary melanomas (17). Huisman et al (28) also reported that expression rhythm of WEE1, a circadian clock-controlled gene (29), was completely disrupted in colorectal liver metastases. Based on these data, the present study presumed that WEE1 Table II.…”
Section: Upregulation Of Wee1 Mrna ----------------------------------mentioning
confidence: 97%
“…The rhythmicity of physiological processes in mammals is achieved by a hierarchical clock organization composed of the central encephalic structures (the master pacemaker housed in the hypothalamic suprachiasmatic nucleus, the lateral eyes, and the pineal gland), plus another series of extraencephalic circadian oscillators located in the peripheral tissues . The genetic and biochemical machinery of this circadian system relies on a set of negative transcriptional/translational feedback cyclic loops of rhythmically or constitutively activated clock genes, that control 10%‐15% of the transcriptome, including important cell cycle and apoptosis regulatory genes. Functionally, the basic expression of clock genes leads to a plethora of recurrent circadian cycles in the form of sine waves of fluctuating events in the integrated physiology of healthy and cancerous tissues, such as CRC …”
Section: Melatonin and The Circadian System: Making The Chronotherapymentioning
confidence: 99%